Editor's Note. - Ogroske, Leon (Writers' Journal)
An introduction is presented in which the editor discusses various reports within the issue on topics including an interview with screenwriter William M. Akers, scheduled book presentation in schools, and guidelines on selling upcoming books through online tools.